Self-Care Management Practices among Diabetics Attending Tertiary Hospitals in Imo East Senatorial District of Imo State - DIBIA, Samuel; NWAGU, Evelyn; ODO, Amelia (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
The purpose of the study was to ascertain the self-care management practices among diabetics attending tertiary hospitals in Imo East senatorial district of Imo State. Five research questions and four null hypotheses guided the study. The study adopted the longitudinal survey design. The population for the study comprised of 17,076 registered diabetics attending tertiary hospitals in Imo East senatorial district, Imo State. The sample for the study consisted of 400 diabetics. The proportionate sampling technique, systematic random sampling and simple random sampling without replacement were used to determine the study sample. A researcher-structured questionnaire titled Self-care management practices Questionnaire was used for data collection. Face validity of the instrument was established through constructive criticism of five experts. The reliability index of .84 was obtained using Cronbach alpha statistics. The researchers administered the instrument by hand. SPSS version 22 software and Excel were used to analyze data. The statistical tools employed for analysis include percentages, mean, standard deviation, t-test and ANOVA. The study revealed that significant differences exist among diabetics’ in the adoption of self-care management practices. In addition, the study found that gender does not significantly affect the adoption of self-care management practices. Based on the findings, recommendations were made among which is that self-care management education and awareness should be increased